Pengaruh Latihan Dribble Zig Zag Terhadap Keterampilan Dribbling Tim Futsal Satria Mandiri Pasuruan - Akhmad Sahal; Fahrial Amiq; Zihan Novita Sari (Pendekar : Jurnal Pendidikan Berkarakter, 2024)
Improving dribbling skills can be done with systematic and regular training so as to get maximum results. Training that can be done is zig-zag dribble using a ball. The purpose of this study was to determine the effect of zig-zag dribble training on the dribbling skills of the Satria Mandiri Pasuruan futsal team. This research method is Pre-Experimental Design research with One Group Pretest-Posttest Design research design, the sample in this study used total sampling of 15 futsal players. The intervention given is the provision of zig-zag dribble training for 16 meetings. Data analysis using paired sample t test and the results showed that zig-zag dribble training affects dribbling skills in the Satria Mandiri Pasuruan futsal team. The pretest results showed that 73.3% of futsal players were in the very poor category, while at the time of the posttest it was 46.6% in the very poor category, so it decreased by 26.7%. Providing regular exercise can significantly affect dribbling skills. It is hoped that training can be given regularly to all players in each training program so that it can continue to improve the dribbling skills of the players.